2002
DOI: 10.1023/a:1019861721160
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 1. The authors' goal was to compare the size and density of Purkinje cells in the cerebellum of subjects with and without autism. Blocks of cerebellum were dissected at autopsy from the brains of age, sex- and postmortem-intervaled (PMI) groups of autistic and normal control individuals (N = 5 per group). Frozen, unfixed blocks were sectioned and stained with 1% cresyl violet. 2. The linear, molecular, granular densities and cross-sectional area of Purkinje cells were measured using computer-assisted image ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
80
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(88 citation statements)
references
References 3 publications
7
80
0
1
Order By: Relevance
“…The involvement of the cerebellum and Purkinje cell dysfunction in autism is a neuro-anatomical measurement that has been explored in humans [28,29,30]. Similar to their findings and other studies using animal models of autism [5,31], we show abnormalities, specifically decreased spine density, in Purkinje cells of the cerebellum.…”
Section: Discussionsupporting
confidence: 89%
“…The involvement of the cerebellum and Purkinje cell dysfunction in autism is a neuro-anatomical measurement that has been explored in humans [28,29,30]. Similar to their findings and other studies using animal models of autism [5,31], we show abnormalities, specifically decreased spine density, in Purkinje cells of the cerebellum.…”
Section: Discussionsupporting
confidence: 89%
“…Third, the two-dimensional Purkinje cell density of normal brain was determined at (16 + 4) cells per mm 2 ( Jeste et al 1984), a value also obtained from our tomographic data. Note, the density of Purkinje cells is reduced by diseases such as schizophrenia, autism, Huntington's disease and other movement disorders ( Jeste et al 1984;Tran et al 1998;Fatemi et al 2002). In summary, there remains no doubt that the micro-features shown in figure 7 are the Purkinje cells, since the location, size, shape and density are very well comparable with the histological results.…”
supporting
confidence: 59%
“…A true measurement of the cell size is therefore impossible. Nevertheless, the spatial resolution of 20 mm, together with the pixel size of 5.1 mm, allows a rough estimate of the diameters of the features detected, which correspond in location and size to the Purkinje cells often visualized in two-dimensional histological slices shown, for instance, in Fatemi et al (2002). Our results agree well with the data of Fatemi et al, who obtained for the cell area (661 + 85) mm 2 from unfixed cerebellar sections but less with the result of stained histological slices by Tran et al (1998), who found (374 + 34) mm 2 .…”
mentioning
confidence: 99%
“…The study by Fatemi et al [25] of the cerebellum of five males with autism with a mean age of 25.2 years and of five age-matched controls revealed a 24% decrease in mean Purkinje cell size but no differences in Purkinje cell densities. The study of the cerebellum of a 16-year-old female diagnosed with autism and severe intellectual deficit showed no alterations in the cerebellum [24].…”
Section: Discussionmentioning
confidence: 99%